Large tangential electric fields in plasmas close to temperature screening. (11th May 2018) - Velasco, J L; Calvo, I; García-Regaña, J M; Parra, F I; Satake, S; Alonso, J A
Abstract: Low collisionality stellarator plasmas usually display a large negative radial electric field that has been expected to cause accumulation of impurities due to their high charge number. In this paper, two combined effects that can potentially modify this scenario are discussed. First, it is shown that, in low collisionality plasmas, the kinetic contribution of the electrons to the radial electric field can make it negative but small, bringing the plasma close to impurity temperature screening (i.e., to a situation in which the ion temperature gradient is the main drive of impurity transport and causes outward flux); in plasmas of very low collisionality, such as those of the large helical device displaying impurity hole (Ida et al (The LHD Experimental Group) 2009 Phys. Plasmas  16 056111; Yoshinuma et al (The LHD Experimental Group) 2009 Nucl. Fusion  49 062002), screening may actually occur. Second, the component of the electric field that is tangent to the flux surface (in other words, the variation of the electrostatic potential on the flux surface), although smaller than the radial component, has recently been suggested to be an additional relevant drive for radial impurity transport. Here, it is explained that, especially when the radial electric field is small, the tangential magnetic drift has to be kept in order to correctly compute the tangential electric field, that can be larger than previously expected. This can have a strong impact on impurity transport, as we illustrate by means of simulations using the newly developed code kinetic orbit-averaging-solver for stellarators, although it is not enough to explain by itself the behavior of the fluxes in situations like the impurity hole.